Mekanisme Pertahanan Diri Tokoh Gunarto dalam Naskah Drama Ayahku Pulang Karya Usmar Ismail - Aditya Bayu Prakosa; Umi Nur Faizah; Rifa uzdhah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Psychological conflicts often arise intensely, as illustrated in Usmar Ismail’s play Ayahku Pulang. The character Gunarto experiences inner turmoil and trauma from family disputes, which trigger various defense mechanisms. This study aims to describe the forms of defense mechanisms exhibited by Gunarto and identify the factors behind their emergence. Using a literacy psychology approach, specifically Sigmund Freud’s psychoanalytic theory, the research elaborates on the character’s psychological dynamics. The qualitative method employed the read-and-record technique, with data analyzed through the Miles and Huberman model involving reduction, classification, and inference. Findings reveal eight defense mechanisms used by Gunarto: denial, repression, avoidance, compartmentalization, rationalization, displacement, sublimation, and identification with the aggressor. Their emergence is influenced by psychological factors such as past trauma, economic hardship, and disharmonious family relationships. In conclusion, Gunarto’s defense mechanisms reflect symptoms of individuals facing trauma and family disharmony. This study demonstrates how a literary-psychological approach enriches understanding of literature as a reflection of the human psyche and reveals more about a character’s inner world.